Cell Therapy Augments Functional Recovery Subsequent to Spinal Cord Injury under Experimental Conditions - Vikram Sabapathy; George Tharion; Sanjay Kumar (Stem Cells International)
The spinal cord injury leads to enervation of normal tissue homeostasis ultimately leading to paralysis. Until now there is no proper cure for the treatment of spinal cord injury. Recently, cell therapy in animal spinal cord injury models has shown some progress of recovery. At present, clinical trials are under progress to evaluate the efficacy of cell transplantation for the treatment of spinal cord injury. Different types of cells such as pluripotent stem cells derived neural cells, mesenchymal stromal cells, neural stem cells, glial cells are being tested in various spinal cord injury models. In this review we highlight both the advances and lacuna in the field of spinal cord injury by discussing epidemiology, pathophysiology, molecular mechanism, and various cell therapy strategies employed in preclinical and clinical injury models and finally we discuss the limitations and ethical issues involved in cell therapy approach for treating spinal cord injury.